Analisis Teori Looking-Glass-Self Cooley: Fenomena Eksistensi Akun Kampus Cantik dan Konstruksinya di Masyarakat - Shafira, Maya; Komariah, Siti; Wulandari, Puspita (The Indonesian Journal of Social Studies, 2022)
The virtual universe always has its role in getting a massive response from society. This research elaborates on thepresence of the @/kampus.cantik account on Instagram media and its relation to self-concept and its construction insociety based on the theory of Symbolic Interaction according to Charles Horton Cooley's view. The research method inthis paper uses a qualitative approach with literature study methods referring to various related literature. This studyuses data collection techniques in the form of analyzing and collecting various literature review materials throughbooks, journals, articles, news websites and other credible sources. The results of the study show that there is relevancebetween Cooley's symbolic interaction theory regarding the Looking Glass Self and self-concept resulting from theappearance of the @/kampus.cantik account accompanied by the circulation of beauty standards created by societyand other external factors. In connection with this social construction, it sharpens beauty standards in society andnormalizes the objectification of women.